2008
DOI: 10.1002/asna.200710827
|View full text |Cite
|
Sign up to set email alerts
|

On the distance to the Ophiuchus star‐forming region

Abstract: The Ophiuchus molecular cloud complex has produced in Lynds 1688 the richest known embedded cluster within ∼300 pc of the Sun. Unfortunately, distance estimates to the Oph complex vary by nearly ∼40% (∼120-165 pc). Here I calculate a new independent distance estimate of 135 ± 8 pc to this benchmark star-forming region based on Hipparcos trigonometric parallaxes to stars illuminating reflection nebulosity in close proximity to Lynds 1688. Combining this value with recent distance estimates from reddening studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 33 publications
8
132
0
Order By: Relevance
“…For this paper we chose RNO 90, a young solar-mass star (G5) with strong water vapor emission in the mid-infrared. RNO 90 is located near (but not inside) the LDN 43 dark cloud roughly 10 degrees from the well-known ρ Ophiuchus young stellar cluster at a distance generally assumed to be that of the cluster of 125 pc 23,24 . The disk is optically thick in the infrared at all radii, and there have been no detections of structural "complications" as seen in more evolved disks, such as TW Hya 25 , although RNO 90 is also not as thoroughly observed.…”
Section: Example Disk: Rno 90mentioning
confidence: 99%
“…For this paper we chose RNO 90, a young solar-mass star (G5) with strong water vapor emission in the mid-infrared. RNO 90 is located near (but not inside) the LDN 43 dark cloud roughly 10 degrees from the well-known ρ Ophiuchus young stellar cluster at a distance generally assumed to be that of the cluster of 125 pc 23,24 . The disk is optically thick in the infrared at all radii, and there have been no detections of structural "complications" as seen in more evolved disks, such as TW Hya 25 , although RNO 90 is also not as thoroughly observed.…”
Section: Example Disk: Rno 90mentioning
confidence: 99%
“…Ophiuchus is considered to be the nearest site of clustered star formation (Wilking & Lada 1983;Motte, André & Neri 1998). Star formation in Ophiuchus is heavily influenced by the nearby Sco OB2 association (Vrba 1977), the centre of which is at a distance of 11 ± 3 pc from Ophiuchus (Mamajek 2008). The southwest/northeast-aligned filamentary streamers from each of the central regions are thought to be due to the effects of this association (Vrba 1977;Loren 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Ophiuchus is considered to be the nearest site of clustered star formation (Wilking & Lada 1983;Motte et al 1998). Star formation in Ophiuchus is heavily influenced by the nearby Sco OB2 association (Vrba 1977), the centre of which is at a distance of 11 ± 3 pc from Ophiuchus (Mamajek 2008). The southwest/northeast-aligned filamentary streamers from each of the central regions are thought to be due to the effects of this association (Vrba 1977;).…”
Section: Discussionmentioning
confidence: 99%
“…De Geus (1992) proposed that star formation proceeded through the three sub-groups of the Scorpius-Centaurus OB association, beginning in the Lower-Centaurus Crux group, followed by the Upper-Centarus Lupus group, and continuing into the Upper Scorpius group. It has long been suggested that the material in the Ophiuchus molecular cloud is being compressed by interaction with a subset of the Upper Scorpius group, the Sco OB2 association (Vrba 1977); furthermore, ascribes the extended filamentary streamers in the Ophiuchus molecular cloud to the effects of the Sco OB2 association, ∼ 11 pc distant (Mamajek 2008 find that the regions of Ophiuchus in closest proximity to the Sco OB2 association have the most active star formation history, and suggest that this is a result of sequential star formation in the region. The Scorpius-Centaurus OB association is shown in Figure 1.5.…”
Section: Sequential Star Formationmentioning
confidence: 99%
See 1 more Smart Citation